Effects of rice-crab culture on nitrogen leaching in rice fields in the north of China - WANG Ang; DAI Danchao; MA Xuzhou; MOU Qun; YU Yongqing; LÜ Weiqun (浙江大学学报. 农业与生命科学版)
In order to explore the leaching loss of nitrogen (N) in the rice-crab culture system, a field experiment was carried out in Panjin, Liaoning Province. A split-plot design with two factors was arranged in this experiment, with crab or without crab as main factors, with or without N fertilizer as sub-factors. The treatments included: 1) rice monoculture without N fertilizer (R0M); 2) rice-crab culture without N fertilizer (R0C); 3) rice monoculture with N fertilization (with N of 160 kg/hm2, R1M); 4) rice-crab culture with N fertilizer (with N of 160 kg N/hm2, R1C). The results showed that NH4+-N was the primary form of N in flooding water, accounting for 50.8% of the total N (TN), while NO3－-N contributed the most to N in leaching water, accounting for 58.5% of TN. Fertilization could significantly increase the concentrations of microbial biomass nitrogen (MBN) in soil, N in flooding and leaching water (P<0.05). The mean concentration of soil MBN in rice-crab field was 17.7% higher than that in rice monoculture. Rearing crab significantly increased the concentration of MBN in soil and reduced leaching losses of NO3－-N (P<0.05), but had little effect on N concentrations in flooding water and leaching losses of NH4+-N and dissolved organic nitrogen (DON). The concentration of NO3－-N in the leaching water showed positive correlation with NO3－-N in flooding water (P<0.01), while the concentration of DON in the leaching water was negatively correlated with the concentration of soil MBN (P<0.01). The cumulative TN leaching of R1M and R1C treatments was 7.6% and 6.3%, respectively, which indicated that the N leaching was not the predominant fertilizer N losses. Rearing crab in rice fields could reduce the cumulative TN leaching by 15.0% at fertilized plots (P<0.05), and 7.2% at no fertilized plots (P>0.05). All in all, the integration of rice and crab cultivation effectively reduces the leaching loss of N fertilizer in rice field.